Reconceptualization of Property in the Era of Digitalization: an Analysis of the Malaysian Anti-Fake News Bill 2018 - Wai Wong, Wai (International Journal of Engineering and Technology, 2018)
Fake news has dominated the social media. In response, the Malaysian Anti-Fake News Bill has been passed swiftly and it brought about awareness as well as other issues like the spread of unverified news and information. Clause 6 of the Bill imposes a duty on the person who is found in ‘possession’ of fake news or such publication that contains fake news. However, the word ‘possession’ is not defined. The objective of this paper is to critically examine the appropriate meaning of ‘possession’ under Clause 6. News in the era of digitalisation is essentially made out of information and digital resources intangible, transferable, shareable and non-exhaustive.  The notion of possession which derived from the traditional concept of property is not applicable to the unique nature of ‘news’ in digital form. There is a need for a reconceptualization of property and the notion of ‘possession’. Such new concept of property should not only describe ‘property’ as things but rather as ‘rights’. The meaning of ‘possession’ should refer to owner’s control, dominance and influence over news and information. This paper further examines how the new notion of possession ought to be applied in the context of Malaysian Anti-Fake News laws.